Bariatric Surgery Modulates Urinary Levels of MicroRNAs Involved in the Regulation of Renal Function - Alkandari, Abdullah; Ashrafian, Hutan; Sathyapalan, Thozhukat; Darzi, Ara; Holmes, Elaine; Athanasiou, Thanos; Atkin, Stephen L.; Gooderham, Nigel J. (Frontiers in Endocrinology, 2019)
Background: Obesity and diabetes cause chronic kidney disease with a common pathophysiology that is characterized by the accumulation of collagen in the extracellular matrix. Recent evidence has implicated the epithelial-to-mesenchymal transition (EMT) as a key step in this pathology with regulation by microRNAs. Weight loss leads to improvements in renal function; therefore, this study hypothesized that bariatric-surgery aided weight loss would lead to changes in urinary microRNAs involved in the regulation of renal function. Materials and methods: Twenty-four bariatric patients undergoing Roux-en-Y gastric bypass and sleeve gastrectomy donated urine preoperatively and at 2-6 months and 1-2 years postoperatively. Urine samples were also obtained from 10 healthy weight and 7 morbidly obese non-surgical controls. Expression levels of kidney microRNAs were assessed in urine and the function of microRNAs was assessed through the in vitro transfection of in HK-2 cells, a kidney proximal tubule cell line. Results: Levels of miR 192, miR 200a and miR 200b were upregulated in urine following bariatric surgery. This increase was consistent across surgical type and diabetes status and was maintained and enhanced with time. Bariatric surgery alters urinary miR 192 expression from levels seen in morbidly obese patients to levels seen in healthy weight control patients. In mechanistic studies, the transfection of miR 192 in HK-2 cells increased miR 200a expression and decreased ZEB2, a key transcriptional promoter of kidney fibrosis. Conclusions: Bariatric surgery increased miR 192 and miR 200 urinary levels, key anti-fibrotic microRNAs that could contribute to a renal-protective mechanism and may be of value as urinary biomarkers following surgery. These findings suggest that urinary microRNAs may represent potential novel biomarkers for obesity-associated renal function.